Use of Ursodeoxycholic Acid and the Risk of Severe Coronavirus Disease 2019 in Elderly Patients with Viral Hepatitis - Okushin, Kazuya; Ikeuchi, Kazuhiko; Saito, Makoto; Kishida, Toshiyuki; Kado, Akira; Fujishiro, Mitsuhiro; Moriya, Kyoji; Yotsuyanagi, Hiroshi; Koike, Kazuhiko; Tsutsumi, Takeya (Internal Medicine, 2025)
Objective Although the management of coronavirus disease 2019 (COVID-19) has improved, chemoprevention remains a challenge. We recently identified that ursodeoxycholic acid (UDCA) is associated with subclinical infection with severe acute respiratory syndrome coronavirus, implying a reduction in the severity of COVID-19. We analyzed a large medical database to assess the utility of UDCA in the reduction of COVID-19 severity. Methods This retrospective observational study was conducted using a large-scale healthcare administrative claims database. We extracted data on patients who were diagnosed with either chronic hepatitis B or C. Among them, patients >50 years of age diagnosed with COVID-19 before December 2022 were analyzed. Patients were divided into two groups: those with or without a prescription of UDCA. The primary outcome was the in-hospital mortality rate. A propensity score-matching analysis was performed using logistic regression. Results A total of 6,413 patients diagnosed with COVID-19 (UDCA group, n =579; non-UDCA group, n =5,834) were analyzed. The median age was 73.0 (IQR, 64.0-81.0) years, and 57.8% of the patients were men. The UDCA group had significantly more complications with liver cirrhosis, hepatocellular carcinoma, type 2 diabetes, and hypertension. The UDCA group had a higher in-hospital mortality rate than the non-UDCA group, even after propensity score matching (7.4% vs. 4.3%, p =0.03), whereas there was no difference in the risks of hospitalization, oxygen therapy, or ventilation. Conclusions Although the observed increase in mortality among UDCA users could have been due to unmeasured confounding factors, UDCA did not reduce the severity of COVID-19 in viral hepatitis patients.